PEMANFAATAN HASIL HUTAN BUKAN KAYU OLEH MASYARAKAT DI DESA LABIAN IRA’ANG DAN DESA DATAH DIAAN DI KABUPATEN KAPUAS HULU - Nono, .; Farahdiba, .; Fahrizal, M (Universitas Tanjungpura, 2017)
Non-timber forest product has big values for community around the forest. People used non- timber forest product for food, traditional medicine, and other uses. The purposes of research are to describe the non-timber forest products used by community in Labian Ira’ang village at Batang Lupar district and Datah Diaan village at Putussibau Utara district in Kapuas Hulu Regency. The methods used in the research were in-depth interview with local people and survey to the forest near the village. Total respondents was 68 peoples; consist of 38 people from Labian Ira’ang village and 30 people from Datah Diaan village. The research was conducted on Juli-August 2016. Result of the research showed that there are three categories of non-timber forest products used by the community. First non-timber forest products as food consist of honey, Sago, Salam Leaf, Enau Fruit, Durian Fruit and Tengkawang Fruit. Second non-timber forest products as handicraft consist of Buloh Betung, Uwe Mataso, Uwe Welaan, Uwe Saga, Limpaso, Akar Bingkai, Daun Paripuk, Daun Kulan, Daun Kernis, Akar Doh Balok, Daun Karipuk, Daun Lutu, Resam, Bangrow, Uwe Saga, Uwe Jalebla, Bulu’ Semeling, Bulu’ Lan, Bulu’ Betung, Bulu’ Bale, Bulu’ Muti, Bulu’ Pesah and Karuing Latex. Third non-timber forest products as medicinal plant consist of Bararan Kunus, Urat Lalamas, Daun Papa, and Kulit Rambean. The product of handicraft was made by the community daily, such as Bubu, Hat and Bidai. These products mostly sell to the market as second income. The community was depending on non-timber forest product and need guidance from the government to conservation the plant. Keywords: Bamboo, honey, Kapuas Hulu regency, non-timber forest product, rattan, sago.